An aminoacylase activity from Streptomyces ambofaciens catalyzes the acylation of lysine on α‐position and peptides on N‐terminal position. Issue 8 (21st May 2018) - Dettori, Léna; Ferrari, Florent; Framboisier, Xavier; Paris, Cédric; Guiavarc'h, Yann; Hôtel, Laurence; Aymes, Arnaud; Leblond, Pierre; Humeau, Catherine; Kapel, Romain; Chevalot, Isabelle; Aigle, Bertrand; et al.
Abstract: The presence of aminoacylase activities was investigated in a crude extract of Streptomyces ambofaciens ATCC23877. First activities catalyzing the hydrolysis of N‐α or ε‐acetyl‐L‐lysine were identified. Furthermore, the acylation of lysine and different peptides was studied and compared with results obtained with lipase B of Candida antarctica (CALB). Different regioselectivities were demonstrated for the two classes of enzymes. CALB was able to catalyze acylation only on the ε‐position whereas the crude extract from S. ambofaciens possessed the rare ability to catalyze the N‐acylation on the α‐position of the lysine or of the amino‐acid in N‐terminal position of peptides. Two genes, SAM23877_1485 and SAM23877_1734, were identified in the genome of Streptomyces ambofaciens ATCC23877 whose products show similarities with the previously identified aminoacylases from Streptomyces mobaraensis . The proteins encoded by these two genes were responsible for the major aminoacylase hydrolytic activities. Furthermore, we show that the hydrolysis of N‐α‐acetyl‐L‐lysine could be attributed to the product of SAM23877_1734 gene.